Fear and temptation : the image of the indigene in Canadian, Australian, and New Zealand literatures - Goldie, Terry (McGill-Queen's University Press, 1989)
Goldie skillfully reveals the ambivalence of white writers to indigenous culture through an examination of the stereotyping involved in the creation of the image of the "Other." The treacherous "redskin" and the "Indian maiden," embodiments of violence and sex, also evoke emotional signs of fear and temptation, of white repulsion from and attraction to the indigene and the land. Goldie suggests that white culture, deeply attracted to the impossible idea of becoming indigenous, either rejects native land claims and denies recognition of the original indigenes, or incorporates these claims into white assertions of native status. After comparing the works of Canadian author Rudy Wiebe and Australian author Patrick White, Goldie concludes by linking the results of his literary analysis to wider cultural concerns, particularly land rights. He shows that literary views of natives, both positive and negative, emphasize the same charac-teristics and he suggests that escape from this limited vision may open the door to solving the problems of native sovereignty.